(untitled) - Toyotaka, Komiya (1956)
This books consists of the following seven parts: Music and drama in the meiji era; Gagaku; The No; The puppet theatre; The kabuki, the shimpa, the shingeki; Japanese music and dance, and occidental music.
Keywords: Music,Drama; Japan,Japan